Julie D. Saba: pediatric oncology is an amazing field that requires both vigilance and medical acumen - Li, Brad (Translational Cancer Research, 2018)
Every day of pediatric oncologists is filled with challenges and a quest to win the day. With a persistently escalating number of pediatric cancer incidence across the world over recent decades, it is believed by many that it is not merely due to the improvements in diagnosis, but also a genuine increase in underlying risk.